Web marketing for the music business - Hutchison, Thomas W. (Focal Press, 2008)
Interested in promoting, selling and distributing music online, got the website but not sure what to do next? is Web Marketing for the Music Business designed to help develop the essential internet presence they want and need. Looking at how the web has developed, providing instructions on how to set up a web site as well as how to use the Internet to promote the artist and the web site. The book includes information on maximizing web sites to increase traffic, online grassroots marketing tactics that will advance an artists career and social networking sites su.
Includes bibliographical references and index. - Print version record
Keywords: Music trade; Internet marketing; Musique; Industrie; Marketing sur Internet